(untitled) (Medicine Today, 2019)
Introduction: Acute myocardial infarction is the leading cause of death. Streptokinase is the most commonly used thrombolytic agent. This study was conducted to compare in-hospital outcome of patients with acute myocardial infarction receiving streptokinase with those not receiving it. Materials & Methods: This descriptive observational study was conducted at Coronary Care Unit, North East Medical College Hospital from 1st July August 2016 to 30th June 2018. 340 patients having acute MI were in- cluded in the study. Two groups were formed: sk group receiving streptokinase and non-sk group not receiving. In-hospital mortality was the primary end point while mechanical and electrical complications were the secondary end points. Results: Among 340 patients, 255(75%) were males and 85(25%) females. Out of those 218 received strep-tokinase, while 122 did not. Mean age of sk group was 53.15±10.30 years and non-sk group 60.5±16 ears. Mean time of arrival to the hospital after symptom onset was 10.41±9.97 hours. SK group patients reached in 5.9±4.76 hours while non-sk group in 19.4±10.5 hours. In-hospital mortality in sk and non-sk group was 19(8.7%) and 25(20.5%) respectively, p=0.002. Complication rate was significantly higher in the non-sk group, 54.09% vs 34.86%, p=0.04. Conclusion: Patients of acute myocardial infarction receiving streptokinase have significantly lesser in-hospital mortality and complications as compared to patients not receiving it. Medicine Today 2019 Vol.31(2): 68-71